Dynamics of Community Behavior Regarding the Use of Traditional Medicine in Treating Chronic Diseases: Ethnographic Study - Soleman Yambormias; Indasah; Ratna Wardani (STRADA : Jurnal Ilmiah Kesehatan, 2025)
The people of Merauke believe that traditional treatment for chronic diseases is safer because it is made from natural ingredients and has been used for generations. Determine knowledge, barrier and benefit factors, and the impact of the use of traditional medicine by the people of Merauke for the treatment of chronic diseases. This ethnographic study was conducted in Merauke in January – June 2024 with 5 users and 2 providers of traditional medicine. Data collection uses a holistic approach by combining observation and interview techniques. The data obtained will be analyzed through a reduction stage where significant information is identified systematically.